FORMULATION DEVELOPMENT AND EVALUATION OF NASAL IN-SITU GEL OF FLUTICASONE PROPIONATE - SAUDAGAR, R. B.; KHANDBAHALE, SARIKA V. (International Journal of Current Pharmaceutical Research, 2017)
Objective: Over a few decades, advances in the in-situ gel technologies have spurred development in may medical and biomedical applications including controlled drug delivery. For locally acting intra nasal drugs, an extended residence time in the nasal cavity is desirable and related to a prolonged effect. The aim of the present work was to design a nasal delivery system with improved mucoadhesive properties that could provide prolonged retention time for the treatment of the allergic rhinitis. Methods: A 32 factorial design was used to investigate the effect of the amount of Poloxamer 188 and carbopol 934 as independent variables. % drug release and mucoadhesive strength were taken as dependent variables. The formulations were tested for gelation study, viscosity study, gel strength, mucoadhesion study, drug content and stability study. Gelation was determined by physical appearance, viscosity study of solution and gel formulations indicated that increase in polymer concentration increase the viscosity. Results: Gel strength was found in the range of 0.55-2.36 sec. The mucoadhesive force in terms of detachment stress increase with an increase in the concentration of carbopol 934. A stability study for optimized formulation as per ICH guideline for 90 d showed no change in pH, drug content and viscosity. Conclusion: The developed in-situ gelling system for Fluticasone Propionate using poloxamer188 in combination with carbopol 934 with improved mucoadhesive properties that could provide prolonged retention time for the treatment of allergic rhinitis.